THE LINGUOGEOGRAPHIC BASIS THE TURKIC LANGUAGES IN WORLD SPACE - С.Б., Бектемировa; Р.А., Авaковa; А.К., Тaусогaровa (Journal of Oriental Studies, 2019)
The formation of literate consciousness in the world space, historical, ethnic, cultural, political, linguistic, geographical features and achievements of modern Turks are the main prerequisites of the Turkic unity. Therefore in the presented scientific project a linguogeographical atlas about the spatial expansion of modern Turkic peoples and an encyclopedic dictionary that is compiled in connection with the study of the languages of the Turkic peoples, encompassing the scientific conceptual, terminological apparatus are one of the main activities on the path to preserving the Turkic unity in the era of globalization. This wide research is carried out not only within the framework of linguistic science, but also at the intersec- tion of anthropology, sociology, cultural studies, cognitive and geographical sciences. Key words: Turkic world, Turkic peoples, Turkic languages, linguogeography, linguocultural studies, Turkic terms, ethnos, geographical atlas, spiritual and cultural value.